Customers’ acceptance towards Musharakah Mutanaqisah based financing product / Nik Natrah Nik Husin - Nik Husin, Nik Natrah (2013)
The purpose of this study is to examine the level of costumers’ acceptance towards Musharakah Muatanqisah based financing product. This study used the development of a multiple linear regression analysis model to identify the significant relationships that affects the customers’ acceptance. Data from questionnaire that develop by researcher were gathered from 100 respondents. There are five main variables that are used to see a relationship with the customers’ acceptance which are customers’ attitude, subjective norm, concept, shari’ah compliance and also pricing. The results indicate that there are relationship between customers’ acceptance with customers’ attitude, concept and also shari’ah compliance. However, there are no relationship between customers’ acceptance with subjective norm and pricing of the product